2017
DOI: 10.1016/j.bbadis.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte-specific deletion of the G protein-coupled estrogen receptor (GPER) leads to left ventricular dysfunction and adverse remodeling: A sex-specific gene profiling analysis

Abstract: Activation of G protein-coupled estrogen receptor (GPER) by its agonist, G1, protects the heart from stressors such as pressure-overload, ischemia, a high-salt diet, estrogen loss, and aging, in various male and female animal models. Due to nonspecific effects of G1, the exact functions of cardiac GPER cannot be concluded from studies using systemic G1 administration. Moreover, global knockdown of GPER affects glucose homeostasis, blood pressure, and many other cardiovascular-related systems, thereby confoundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 57 publications
8
61
0
Order By: Relevance
“…Total RNA was isolated from cardiomyocytes using the RNeasy Lipit Tissue Mini Kit (Qiagen, Inc., Germantown, MD) and further purified using RNeasy MinElute Cleanup Kit (Qiagen, Inc., Germantown, MD) followed by quality assessment on an Agilent 2100 bioanalyzer, as previously described (Wang, Sun, et al, ). Relative quantification of mRNA levels by real‐time qPCR for angiotensinogen, renin, ACE, ACE2, chymase, AT1R, AT2R, and Mas was performed using a SYBR Green PCR kit (Qiagen, Inc., Germantown, MD), as previously described (Wang et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was isolated from cardiomyocytes using the RNeasy Lipit Tissue Mini Kit (Qiagen, Inc., Germantown, MD) and further purified using RNeasy MinElute Cleanup Kit (Qiagen, Inc., Germantown, MD) followed by quality assessment on an Agilent 2100 bioanalyzer, as previously described (Wang, Sun, et al, ). Relative quantification of mRNA levels by real‐time qPCR for angiotensinogen, renin, ACE, ACE2, chymase, AT1R, AT2R, and Mas was performed using a SYBR Green PCR kit (Qiagen, Inc., Germantown, MD), as previously described (Wang et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…It is unlikely that these discrepancies are due to compensatory increases in the expression of classical ERs, as both Wang et al . () and Martensson et al . () reported no change in mRNA abundance of ERα and ERβ.…”
Section: G Protein‐coupled Oestrogen Receptormentioning
confidence: 86%
“…Intriguingly, Wang et al . () report that cardiomyocyte‐specific deletion of GPER causes left ventricular (LV) dysfunction and remodelling in both sexes but a male‐specific inflammatory response. This result is difficult to reconcile with the above studies, which show no deleterious cardiovascular effects in male mice with global GPER gene deletion, especially considering the similar expression of cardiac GPER between the sexes (Deschamps and Murphy, ).…”
Section: G Protein‐coupled Oestrogen Receptormentioning
confidence: 99%
“…Elevations in LV filling pressure initially compensate, but eventually pulmonary congestion develops as a result of increased left atrial (LA) pressure (10). While a wide range of diastolic function parameters can be obtained by Doppler-echocardiography (11), a simple composite of blood flow and tissue Doppler measures, as reviewed by ourselves and others (12)(13)(14) can sensitively detect and predict diastolic dysfunction in humans (15)(16)(17), non-human primates (18,19), and preclinical rodent research models (20)(21)(22)(23)(24)(25). The spectrum of diastolic dysfunction is portrayed schematically in Figure 1.…”
Section: What Is Diastolic Dysfunction?mentioning
confidence: 99%
“…Initial work showed that administration of the GPER agonist G1 prevents diastolic dysfunction and LV remodeling in OVX (25) and salt-loaded (65) mRen2.Lewis rats. To tease out more precise information about the functional role of GPER in the heart, we generated a novel conditional mouse model where GPER was specifically deleted in cardiomyocytes (23). Therefore, the remainder of the review FIGURE 2 | GPER in the functional circle of diastology of the female heart.…”
Section: Estrogen Receptors In the Heartmentioning
confidence: 99%